Broadband 2 × 2 multimode interference coupler for mid-infrared wavelengths - Stirling, Callum J.; Halir, Robert; Sánchez-Postigo, Alejandro; Qu, Zhibo; Reynolds, Jamie D.; Soler Penadés, Jordi; Murugan, Ganapathy Senthil; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Molina-Fernández, Íñigo; Mashanovich, Goran Z.; Nedeljkovic, Milos (Optical Publishing Group, 2021)
Beam splitters are core components of photonic integrated circuits and are often implemented with multimode interference couplers. While these devices offer high performance, their operational bandwidth is still restrictive for sensing applications in the mid-infrared wavelength range. Here we experimentally demonstrate a subwavelength-structured 2×2 multimode interference coupler with high performance in the 3.1−3.7µm range, doubling the bandwidth of a conventional device.
Versión aceptada del artículo publicado en Optics Letters (https://doi.org/10.1364/OL.439985).
Keywords: Circuitos integrados; silicon photonics; subwavelength grating metamaterials; multimode interference couplers